Meaning makers at work: how do above average and average students make sense of English and Bahasa literary texts? - Sheikh Ahmad, Ismail; A. Ghani, Muhammad Faizal (House of Pakistani Educationist, 2014)
This study seeks to explore the relationship between eight types of comprehension questions and eight types of coded discourse units which are based on the eight subskills of Lunzer and Gardner (1979). In general each reasoning strategy used by selected above average and average readers in response to each test item is interpreted and categorized as one of the eight sub-skills. Currently, no similar reading research has been done in this area. The findings of this table suggest that both the above average and average readers' reasoning strategies, in all the L1 and L2 texts, reflect the usage of all the various Discourse Types (DTs) with the exception of DT 6 (M) and DT 7 (S) which are under utilized by both groups of readers (see rows 6 and 7 in Table 25). The good readers' responses seem to be more specific and focus on every single question type itself. The higher context-specific FSI scores of the good readers, as seen diagonally, reflect the regulatory power of the readers in monitoring their comprehension. It also suggests that the comprehension discourse strategies of the readers are more active in their attempts to reason out their understanding of the questions. This may suggest that the good readers' mastery of the content of the texts make them rely less on the DT Forming Judgment (J). These findings seem to indicate that the above average readers evidence a greater reflection on every QT (except on QT(J)) than the average readers. Quantitatively, the above average readers are found to be different in their reflections of their reasoning strategies from the average readers. The reasoning processes of the above average readers are much more focused on each QT than those of the average readers. This shows that the good readers were able to activate their reasoning processes within the sphere of each of the QTs individually, relying less on other skills. This phenomenon strongly suggests that instruction in improving poor readers' comprehension monitoring strategies should teach this unique strategy of the good readers. In other words, reading teachers should improve the average and poor readers' awareness and knowledge in comprehension strategies because logically, an increase in awareness of strategic knowledge may improve pupils' performances on reading comprehension tasks. Whether such differences, as seen by the patterns of the Factor Specificity Index (FSIs), qualitatively reflect better and more effective reasoning strategies by the above average readers than by the average readers may need further investigation.